Skala Usaha dan Umur Usaha yang Mempengaruhi Penggunaan Sistem Informasi Akuntansi (Studi Empris Pada Toko Kue dan Roti di Kota Padang) - mike kusuma dewi (JURNAL PUNDI, 2018)
This study aims to determine the effect of business scale and business age on the use of accounting information systems in bakeries and cakes in the city of Padang, namely the business scale and business age. From the results of research conducted can be formulated that the larger the business scale and business age, the higher the need for the use of accounting information systems, especially in the types of bakery and cake business in the city of Padang. The method used is to spread questionnaires to 19 The existing cake and bread shops, only as many as 11 shops were willing to fill out the questionnaires provided and also had applied the Accounting information system to their operational activities in Padang City and the respondents who successfully filled out the questionnaires were 70 people. From the results of the study can be explained that the variable (X1) business scale has a significant positive effect on the use of accounting information systems where the significance value is 0.016 <0.05, as well as Variables (X2) Business Age has a significant positive effect on the use of accounting information systems where the significance value is 0.004 <0.05. The data processing tool that is used is to use SPSS Ver.23